Giardia and growth impairment in children in high-prevalence settings: consequence or co-incidence?. Issue 5 (12th October 2022) - Dougherty, Michael; Bartelt, Luther A.
Abstract : Purpose of review: Giardia is a common intestinal parasite worldwide, and infection can be associated with clear, and sometimes persistent symptomatology. However, in children in high-prevalence settings, it is most often not associated with or is perhaps even protective against acute diarrhea. Nonetheless, recent longitudinal studies in high-prevalence settings increasingly identify an association with long-term outcomes that has been difficult to discern. Recent findings: Recent studies have made progress in disentangling this apparent paradox. First, prospective, well characterized cohort studies have repeatedly identified associations between Giardia infection, gut function, and child growth. Second, experimental animal and in-vitro models have further characterized the biological plausibility that Giardia could impair intestinal function and subsequently child development through different pathways, depending upon biological and environmental factors. Finally, new work has shed light on the potential for Giardia conspiring with specific other gut microbes, which may explain discrepant findings in the literature, help guide future higher resolution analyses of this pathogen, and inform new opportunities for intervention. Summary: Recent prospective studies have confirmed a high, if not universal, prevalence of persistent Giardia infections in low-and-middle income countries associated with child-growth shortfalls and altered gut permeability. However, the predominance of subclinical infections limits understanding of the true clinical impact of endemic pediatric giardiasis, and global disease burdens remain uncalculated. Integrating the role of Giardia in multipathogen enteropathies and how nutritional, microbial, metabolic, and pathogen-strain variables influence Giardia infection outcomes could sharpen delineations between pathogenic and potentially beneficial attributes of this enigmatic parasite.